2011
DOI: 10.1037/a0022582
|View full text |Cite
|
Sign up to set email alerts
|

Convergent and divergent responses to emotional displays of ingroup and outgroup.

Abstract: In the present research, we test the assumption that emotional mimicry and contagion are moderated by group membership. We report two studies using facial electromyography (EMG; Study 1), Facial Action Coding System (FACS; Study 2), and self-reported emotions (Study 2) as dependent measures. As predicted, both studies show that ingroup anger and fear displays were mimicked to a greater extent than outgroup displays of these emotions. The self-report data in Study 2 further showed specific divergent reactions t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
245
6
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(270 citation statements)
references
References 53 publications
17
245
6
2
Order By: Relevance
“…So too with mimicry and contagion. The consensus is that pre-existing rapport and/or a desire to affiliate (see Aylward, 2008;Bailenson & Yee, 2005;and Hess & Fischer, 2013, for a summary of this research), similarity (see Stockert, 1994, for a summary of this research), and group membership do indeed have a profound impact on mimicry and contagion (Chartrand & Lakin, 2013;Hess & Fischer, 2013;van der Schalk et al, 2011). Yet, in our own work and that of our graduate students, we have come to recognize that these factors might be weaker than one might expect.…”
Section: Liking Similarity and Ingroup Versus Outgroup Statusmentioning
confidence: 98%
“…So too with mimicry and contagion. The consensus is that pre-existing rapport and/or a desire to affiliate (see Aylward, 2008;Bailenson & Yee, 2005;and Hess & Fischer, 2013, for a summary of this research), similarity (see Stockert, 1994, for a summary of this research), and group membership do indeed have a profound impact on mimicry and contagion (Chartrand & Lakin, 2013;Hess & Fischer, 2013;van der Schalk et al, 2011). Yet, in our own work and that of our graduate students, we have come to recognize that these factors might be weaker than one might expect.…”
Section: Liking Similarity and Ingroup Versus Outgroup Statusmentioning
confidence: 98%
“…Further evidence of prejudice affecting bodily interaction with others come from studies of mimicry, the unconscious tendency we have to imitate the facial and bodily movements of others, which is thought to be a method of increasing affiliation (Chartrand & Lakin, 2013;Hale & Hamilton, 2016). This tendency to mimic another person is reduced when the person belongs to a social or racial out-group (Bourgeois & Hess, 2008;Liebert et al, 1972;Losin, Iacoboni, Martin, Cross, & Dapretto, 2012;Neely, Heckel, & Leichtman, 1973;van der Schalk et al, 2011;Weisbuch & Ambady, 2008), and the extent to which we mimic out-group members is negatively related to our implicit prejudice against them. For example, Yabar, Johnston, Miles and Peace (2006) found greater mimicry of a non-Christian confederate than of a Christian confederate among non-Christian participants.…”
Section: Prejudice and The Bodily Selfmentioning
confidence: 99%
“…Since the LPP has been associated with the intrinsic relevance of stimuli (Schupp et al, 2004), our result may reflect a higher relevance of sad faces when they are from own-aged rather than otheraged individuals. Happiness may differ from sadness in this respect because a smile may strongly signal affiliation, and thereby overrule group boundaries (van der Schalk et al, 2011), rendering happy faces of own-aged and other-aged individuals equally relevant. This is in line with previous reports of attenuated in-group effects for happy faces.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with previous reports of attenuated in-group effects for happy faces. Some studies examining facial mimicry-that is, the imitation of emotional expressions-have shown in-group effects for negative, but not for positive, emotions (Bourgeois & Hess, 2008;van der Schalk et al, 2011), and the own-race effect in emotion decoding accuracy was smallest for happiness (see Elfenbein & Ambady, 2002, for a review). Also in line with this assumption, in a recent study of our own group, we found an emotion-specific own-age advantage in decoding accuracy for sadness, but not for happiness (Fölster, Hess, Hühnel, & Werheid, 2015).…”
Section: Discussionmentioning
confidence: 99%